Usability evaluation of e-learning applications - Царик, О. Р. (Proceedings of National Aviation University (archive), 2013)
Purpose is to justify the importance and the necessity of usability evaluation of e-learning applications. The method of study is definition of the concept of usability, analysis of existing methods and criteria for usability evaluation, as well as determining the parameters that are necessary to carry out the proper usability evaluation of e-learning applications. The basic methods for usability evaluating, as well as the criteria by which to conduct this assessment are determined. It is established that the assessment of usability of e-learning applications is an integral and important part of the development of life cycle of most tools and systems. Usability Evaluation enables the creation of e-learning systems that will be used to support its users, namely those who teach and those who learn. Development of appropriate methodologies for usability evaluating of e-learning is the key to creating effective, productive and high suitable educational systems.